Tres Tristes Tigres - Munoz, David (Spain, 2010)
This film tells the story of three men from the rural village of Rajbari in Bangladesh, who traveled to the Middle East in the hope of making money. The construction boom in the Middle East has brought in 832,000 Bangladeshi workers. The labor abuse and illegal contracting, which are accepted by the Bangladeshi government and tolerated by the International Labor Organization, has caused thousands of broken families and destroyed countless dreams.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films